Discovery of a potent and selective covalent inhibitor and activity-based probe for the deubiquitylating enzyme UCHL1, with anti-fibrotic activity - Panyain,N; Godinat,A; Lanyon-Hogg,T; Lachiondo-Ortega,S; Will,EJ; Soudy,C; Mondal,M; Mason,K; Elkhalifa,S; Smith,L; Harrigan,JA; Tate,EW (Journal of the American Chemical Society, 2020)
Ubiquitin carboxy-terminal hydrolase L1 (UCHL1) is a deubiquitylating enzyme which is proposed as a potential therapeutic target in neurodegeneration, cancer, and liver and lung fibrosis. Herein we report the discovery of the most potent and selective UCHL1 probe (IMP-1710) to date based on a covalent inhibitor scaffold and apply this probe to identify and quantify target proteins in intact human cells. IMP-1710 stereoselectively labels the catalytic cysteine of UCHL1 at low nanomolar concentration in cells. We further demonstrate that potent and selective UCHL1 inhibitors block pro-fibrotic responses in a cellular model of idiopathic pulmonary fibrosis, supporting the potential of UCHL1 as a potential therapeutic target in fibrotic diseases.